Efektivitas Pemanfaatan Game Based Learning Berbasis Educandy untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Kelas XII pada Pembelajaran Pendidikan Pancasila di SMAN 18 Surabaya - Naning Nawangsih; Raden Roro Nanik Setyowati (Indo Publishing, 2026)
This study was conducted to examine the effectiveness of the Game-Based Learning (GBL) model implemented through Educandy in improving the cognitive learning outcomes of twelfth-grade students in Pancasila Education at SMAN 18 Surabaya. This study employed a quantitative method with a quasi-experimental design by comparing learning outcomes between the experimental group and the control group. As a form of treatment, the experimental group received instruction using the Educandy-based Game-Based Learning (GBL) model. In contrast, the control group continued to participate in the learning process through conventional teaching methods. To collect the data, this study used two main instruments: cognitive tests to measure students’ learning outcomes before and after the treatment, and questionnaires to describe students’ responses during the learning process. The significance of the difference in learning outcomes between the experimental and control groups was tested using the Independent Samples t-Test. To measure the extent of improvement in students’ cognitive abilities, this study also applied the Normalized Gain (N-Gain) score as a parameter of the effectiveness of the intervention. The results of the statistical analysis showed a Sig. (2-tailed) value of 0.000, which was below the 0.05 significance threshold. This finding confirms a significant difference in students’ learning outcomes between the experimental group and the control group. The experimental class achieved an average posttest score of 90.13, reflecting an improvement of 36.58 points from the pretest score of 53.55. In comparison, the control group obtained an average posttest score of 86.97, indicating an increase of 30.79 points from the initial pretest average of 56.18. Based on the N-Gain analysis, the experimental group obtained a score of 0.71, which falls within the high category, whereas the control group achieved a score of 0.57, which is classified as moderate. In addition, 94.21% of students gave positive responses to the use of Educandy, indicating that the learning medium was categorized as highly effective. Based on these findings, it can be concluded that the implementation of the Game-Based Learning (GBL) model through the Educandy platform is more effective in improving students’ cognitive learning outcomes than conventional teaching methods.